Bariatric Surgery Complications : The Medical Practitioner's Essential Guide - Blackstone, Robin P. (Springer International Publishing : Imprint: Springer, 2017)
This text provides a background of scientific evidence to understand the complications that occur after bariatric surgery for all providers responsible for care after surgical intervention. Written by experts and based on current peer reviewed literature, the text provides a focused approach to the identification and treatment of bariatric surgery complications. To establish a context for providers, the initial section concentrates on presenting the current procedures as well as risks and expected benefits of each with an emphasis on mechanism of action. It examines the issue of weight regain from the aspect of heterogeneity in order to present the perspective that every procedure has risk of weight regain. The text provides guidance to those front line providers who manage acute emergencies and chronic long term problems. State of the art management of complications like leaks, bleeding, ulcers, blood clots and pneumonia are discussed for all procedures in addition to the management of rapid remission of obesity related disease like Type 2 Diabetes and coagulopathies (Leiden Factor V, Protein C and S) that occur commonly in patients with obesity. Each chapter features a review of the current literature in an easy to reference table format and where appropriate an algorithm to focus the reader on the process of care for any given presenting sign or symptom. Bariatric Surgery Complications will be of great value to fellows in minimally invasive surgery, general surgeons, emergency room physicians, gastroenterologists, primary care physicians, medical students and residents in surgery rotations, integrated health personnel.
Keywords: Medicine.; Gastroenterology.; Surgery.; Minimally invasive surgery.; Emergency medicine.; elektronické knihy; electronic books